The impact of whatsapp marketing on brand loyalty and sales conversion: Roles of customer engagement, chatbots, and real-time communication - Surjadeep Dutta; Arunava Mookherjee; Tisha Biswas; Anindita Sinha (CV. SPDFHarmony, 2026)
Background: The worldwide expansion of WhatsApp into a global communication platform has created new digital marketing opportunities which enable businesses to establish direct contact with customers through a real-time interactive communication method. WhatsApp delivers better message open rates than standard email marketing methods which makes it suitable for personalized interactive communication especially in developing countries such as India.Aims: The research aims to evaluate how WhatsApp marketing strategies impact customer engagement results. The study investigates how customer engagement connects to brand loyalty within the framework of WhatsApp marketing.Methods: The study used conceptual framework to find out how successful WhatsApp Marketing Strategies are in improving customer engagement and increasing business performance. The secondary Data has been collected from SCOPUS, EBSCO, PROQUEST, IGI Global, IEEE Databases and Journals. Most of the references has been taken from the Year 2018-2025.Result: The research results demonstrate that WhatsApp marketing techniques produce better customer engagement results, which serve as the main connection that affects business performance. The system provides real-time communication together with multimedia content and Chatbot automation to improve responsiveness while delivering personalized experiences, which results in more customer interactions and better response rates to call-to-action messages. The use of automation tools enables businesses to achieve better operational results and enhanced customer satisfaction.Conclusion: The research demonstrates that WhatsApp marketing tools need to be used strategically because their Chatbot automation and interactive messaging features help businesses to boost customer interaction and buying likelihood. The first requirement for businesses to achieve lasting success with WhatsApp marketing needs them to build customer trust through effective privacy protection and data security measures.